Android Malware on the Rise - Spreitzenbarth, Michael; Freiling, Felix (2012)
It is now well-known that, for various reasons, Android has become the leading OS for smartphones with more than 50% of worldwide market share within only a few years. This fast growth rate also has an evil side. Android brought backdoors and trojans to the yet spared Linux world with growth rates of over 3000% and more than 13000 malicious applications. These malicious apps are only seldom obfuscated and very basic in their functionality. In this technical report, we give a short overview of the existing malware families and their main functionality. As an example, we present the results of reverse engineering two paradigmatic malware samples of the Bmaster and FakeRegSMS families. These samples were chosen because they try to implement the first very simple approaches of obfuscation and behavior hiding. We conclude with discussing the following questions: How do you get infected? What was the main goal for malware authors in recent malicious applications? Is real obfuscation coming to Android? And finally, how does the future of malware look like? <br
UnivIS-Import:2016-06-30:Pub.2012.tech.IMMD.lehrst.androi
Keywords: Android; Malware; Trojan; Virus